Psychological distance and fear of crime: Towards a new understanding of risk perception formation - Mellberg, Jacques (Journal of criminology, 2022)
The current study seeks to enhance the theoretical development of fear of crime by exploring the complex cognitive processes involved in risk perception formation. We apply Trope and Liberman?s construal level theory (CLT) of psychological distance to understand how and why these complex cognitive processes might shape an individual?s worry about crime. We pilot survey measures designed to capture perceptions of psychological distance and worry about crime using a convenience sample of N?=?265 residents from Townsville, Queensland, Australia. Results of confirmatory factor analyses (CFA) reveal that these new measures have good scaling properties and that each dimension of psychological distance is empirically distinct. Multiple linear regression demonstrates that temporal, social and hypothetical psychological distance predicted worry at a statistically significant level, however, spatial distance was in the expected direction but was not statistically significant. These findings suggest that CLT is an appropriate lens to understand how individuals perceive their risk of criminal victimisation, but further research is needed to refine spatial distance survey measures. We recommend future research explores how psychological distance may interact with other well-known correlates of worry, such as age, gender and ethnicity.